Kubernetes in the data center : LiveLessons (LiveLessons (Indianapolis, Ind.), 2020)
"Kubernetes in the Data Center LiveLessons focuses on using the fundamental Kubernetes components and learning how they are installed. The goal is to help you understand what the components are so when troubles arise you have the tools to be able to fix them. The course is primarily made up of instruction and demonstrations delivered by a seasoned expert, Vallard Benincosa. Vallard, who has experience working with Cisco and IBM, is currently a senior engineer at a small startup called Zenabi. He helped develop a Kubernetes certification for the Linux foundation and has been using Kubernetes since 2015. Kubernetes in the Data Center LiveLessons walks you through Kubernetes on prem, hardware, and Linux configurations, installation, applications storage, and networking. It also gets in to running Kubernetes, as well as monitoring and securing it. The course covers a wide gambit of technical areas and explores many of the exciting Kubernetes opensource add-ons to make your system more complete. This includes Kubernetes, Docker, Ubuntu Linux, Minio, Ceph, and many networking concepts such as overlay networks, service meshes, load balancing, ingress controllers, and proxies."--Resource description page